The Implementation of Waqf Law within the Framework of Indonesia's Legal State: An Analysis of Pancasila Values - Miskari (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2024)
This study aims to explore the preservation of waqf in Indonesia, which plays a crucial role in supporting social welfare and community development, while considering Pancasila as the state ideology. The research seeks to analyze how Islamic legal principles are integrated into waqf preservation in relation to Pancasila values and to understand the interaction between these two value systems within the national legal framework. The study employs a qualitative analysis method with a literature review approach. Data is gathered through an examination of relevant laws and government regulations, as well as fatwas and guidelines concerning waqf and pancasila. The analysis focuses on evaluating the connection between Islamic principles related to waqf preservation and the implementation of Pancasila values within the Indonesian legal system. The research aims to identify and explain the relationship between Islamic legal principles regarding waqf and Pancasila values and to assess how Pancasila values support and enhance the preservation of waqf in Indonesia. The findings reveal that Pancasila values, particularly the principles of social justice and humanity, align with Islamic principles in the preservation of waqf. Pancasila serves as an ethical framework that supports fair and transparent waqf implementation, ensuring that waqf not only complies with Islamic law but also contributes to sustainable social welfare. The study also identifies that integrating Islamic principles with Pancasila values in waqf management can improve the effectiveness of waqf preservation and strengthen the legal and social foundation in Indonesia.